Impulse Control Behaviors in Parkinson's Disease: Drugs or Disease? Contribution From Imaging Studies - De Micco, Rosa; Russo, Antonio; Tedeschi, Gioacchino; Tessitore, Alessandro (Frontiers in Neurology, 2018)
Impulse control behaviors (ICB) are recognized as non-motor complications of dopaminergic medications in patients with Parkinson’s disease (PD). Compelling evidence suggests that ICB are not merely due to the PD-related pathology itself. Several risk factors have been identified, either demographic, clinical, genetic or neuropsychological. Neuroimaging studies have yielded controversial results regarding ICB correlates in PD and still it is not clear whether they can be triggered by the PD biology or the dopaminergic treatment stimulation. We provided an overview of the imaging studies that offered the most relevant insights into the debate about the role of drugs and disease in ICB pathophysiology. Understanding neural correlates and potential predisposing factors of these severe neuropsychiatric symptoms will be crucial to guide clinical practice and to foster preventive strategies.